A generic interface to reduce the efficiency-stability-cost gap of perovskite solar cells - Hou, Yi; Du, Xiaoyan; Scheiner, Simon; McMeekin, David P.; Wang, Zhiping; Li, Ning; Killian, Manuela; Chen, Haiwei; Richter, Moses; Levchuk, Ievgen; Schrenker, Nadine; Spiecker, Erdmann; et al. (Science, 2017)
A major bottleneck delaying the further commercialization of thin-film solar cells based on hybrid organohalide lead perovskites is the interface losses in state-of-the-art devices. We present a generic interface architecture that combines solution-processed, reliable, and cost-efficient hole-transporting materials, without compromising efficiency, stability or scalability of perovskite solar cells. Tantalum doped tungsten oxide (Ta-WOx)/conjugated polymer multilayers offer a surprisingly small interface barrier and form quasi-ohmic contacts universally with various scalable conjugated polymers. Using a simple regular planar architecture device, Ta-WOx doped interface-based perovskite solar cells achieve maximum efficiencies of 21.2% and combined with over 1000 hours of light stability based on a self-assembled monolayer. By eliminating additional ionic dopants, these findings open up the whole class of organics as scalable hole-transporting materials for perovskite solar cell

A novel approach for preparation and in situ tensile testing of silica glass membranes in the TEM - Mackovic, Mirza; Przybilla, Thomas; Dieker, Christel; Herre, Patrick; Romeis, Stefan; Stara, Hana; Schrenker, Nadine; Peukert, Wolfgang; Spiecker, Erdmann (Frontiers in Materials, 2017)
The mechanical behavior of glasses in the micro- and/or nanometer regime increasingly gains importance in nowadays modern technology. However, suitable small scale preparation and mechanical testing approaches for a reliable assessment of the mechanical properties of glasses still remain a big challenge. In the present work, a novel approach for site-specific preparation and quantitative in situ tensile testing of thin silica glass membranes in the transmission electron microscope is presented. Thereby, advanced focused ion beam techniques are used for the preparation of nanoscale dog bone shaped silica glass specimens suitable for in situ tensile testing. Small amounts of gallium are detected on the surface of the membranes resulting from redeposition effects during the focused ion beam preparation procedure. Possible structural changes of silica glass upon irradiation with electrons and gallium ions are investigated by controlled irradiation experiments, followed by a structural analysis using Raman spectroscopy. While moderate electron beam irradiation does not alter the structure of silica glass, ion beam irradiation results in minor densification of the silica glass membranes. In situ tensile testing of membranes under electron beam irradiation results in distinctive elongations without fracture confirming the phenomenon of superplasticity. In contrast, in situ tensile testing in the absence of the electron beam reveals an elastic/plastic deformation behavior, and finally leads to fracture of the membranes. The Young’s moduli of the glass membranes pulled at beam off conditions in the TEM are comparable with values known for bulk fused silica, while the tensile strength is in the range of values reported for silica glass fibers with comparable dimensions. The impact of electron beam irradiation on the mechanical properties of silica glass membranes is further discussed. The results of the present work open new avenues for dedicated preparation and nanomechanical characterization of silica glasses, and further contribute to a fundamental understanding of the mechanical behavior of such glasses when being scaled down to the nanometer regim
Keywords: Silica glass; in situ TEM; in situ nanomechanical testing; Mechanical Properties; Electron beam irradiation; superplasticity; FIB; Raman spectroscopy

Balancing electrical and optical losses for efficient 4-terminal Si–perovskite solar cells with solution processed percolation electrodes - Ramírez Quiroz, César Omar; Shen, Yilei; Salvador, Michael Filipe; Forberich, Karen; Schrenker, Nadine; Spyropoulos, Georgios; Heumüller, Thomas; Wilkinson, Benjamin; Kirchartz, Thomas; Spiecker, Erdmann; Verlinden, Pierre J.; Zhang, Xueling; et al. (Journal of Materials Chemistry A, 2018)
The unprecedented rise in efficiency of perovskite-based photovoltaics has sparked interest in semitransparent devices, particularly for tandem structures. Despite promising reports regarding efficiency and reduced parasitic absorption, many devices still rely on processes from the gas phase, compromising both applicability and cost factors. Here, we report all-solution perovskite solar cells with improved infrared transparency ideally suited as top-cells for efficient multi-junction device configurations. We demonstrate the functionality of copper(I) thiocyanate as antireflective layer and as selective contact between the transparent conductive oxide and the perovskite. This concept allows us to fabricate an opaque device with steady state efficiency as high as 20.1%. By employing silver nanowires with robust environmental stability as the bottom electrode, we demonstrate different regimes of device performance that can be described through a classical percolation model, leading to semi-transparent solar cells with efficiencies of up to 17.1%. In conjunction with the implementation of an infrared-tuned transparent conductive oxide contact deposited on UV-fused silica, we show a full device average transmittance surpassing 84% between 800 and 1100 nm (as opposed to 77% with PEDOT:PSS as the selective contact). Finally, we mechanically stacked optimized perovskite devices on top of high performing PERL and IBC silicon architectures. The measured imputed output efficiency of the 4-terminal perovskite–silicon solar cell was 26.7% and 25.2% for the PERL–perovskite and IBC–perovskite, respectivel

Direct observation of dislocation formation and plastic anisotropy in Nb2AlC MAX phase using in situ nanomechanics in transmission electron microscopy - Kabiri, Yoones; Schrenker, Nadine; Müller, Julian; Mackovic, Mirza; Spiecker, Erdmann (Scripta Materialia, 2017)
We report on the direct observation of nucleation and propagation of basal plane dislocations in Nb2AlC, a member of MAX phases, using nanomechanical testing inside a transmission electron microscope. Different loading directions with respect to the basal plane resulted in completely different plastic response due to the pronounced anisotropy of the layered crystal. Discrete dislocation activities were correlated to distinct events in the force-displacement curves. In situ observations together with post-mortem contrast analyses of deformed regions show no indication of cross-slip or entanglement of dislocations during the indentations.
Keywords: Transmission electron microscopy (TEM); Nanoindentation; Dislocation nucleation; Mechanical properties; MAX phases

Mechanical and Electrical Failure of Silver Nanowire Electrodes: A Scale Bridging In Situ Electron Microscopy Study - Schrenker, Nadine; Schweizer, Peter; Moninger, Marco; Karpstein, Nicolas; Mackovic, Mirza; Spyropoulos, Georgios; Göbelt, Manuela; Christiansen, Silke; Brabec, Christoph; Spiecker, Erdmann (Microscopy and Microanalysis, 2019)

Mechanical Failure of Transparent Flexible Silver Nanowire Networks for Solar Cells using 3D X-Ray Nano Tomography and Electron Microscopy - Englisch, Silvan; Wirth, Janis; Schrenker, Nadine; Tam, Kai Cheong; Egelhaaf, Hans-Joachim; Brabec, Christoph; Spiecker, Erdmann (Microscopy and Microanalysis, 2018)

Microscopic Deformation Modes and Impact of Network Anisotropy on the Mechanical and Electrical Performance of Five-fold Twinned Silver Nanowire Electrodes - Schrenker, Nadine; Xie, Zhuocheng; Schweizer, Peter; Moninger, Marco; Werner, Felix; Karpstein, Nicolas; Mackovic, Mirza; Spyropoulos, Georgios; Göbelt, Manuela; Christiansen, Silke H.; Brabec, Christoph; Bitzek, Erik; et al. (ACS nano, 2020)
Silver nanowire (AgNW) networks show excellent optical, electrical, and mechanical properties, which make them ideal candidates for transparent electrodes in flexible and stretchable devices. Various coating strategies and testing setups have been developed to further improve their stretchability and to evaluate their performance. Still, a comprehensive microscopic understanding of the relationship between mechanical and electrical failure is missing. In this work, the fundamental deformation modes of five-fold twinned AgNWs in anisotropic networks are studied by large-scale SEM straining tests that are directly correlated with corresponding changes in the resistance. A pronounced effect of the network anisotropy on the electrical performance is observed, which manifests itself in a one order of magnitude lower increase in resistance for networks strained perpendicular to the preferred wire orientation. Using a scale-bridging microscopy approach spanning from NW networks to single NWs to atomic-scale defects, we were able to identify three fundamental deformation modes of NWs, which together can explain this behavior: (i) correlated tensile fracture of NWs, (ii) kink formation due to compression of NWs in transverse direction, and (iii) NW bending caused by the interaction of NWs in the strained network. A key observation is the extreme deformability of AgNWs in compression. Considering HRTEM and MD simulations, this behavior can be attributed to specific defect processes in the five-fold twinned NW structure leading to the formation of NW kinks with grain boundaries combined with V-shaped surface reconstructions, both counteracting NW fracture. The detailed insights from this microscopic study can further improve fabrication and design strategies for transparent NW network electrodes.<br
Keywords: silver nanowire; five-fold twinning; transparent electrode; buckling; kinks; transmission electron microscopy; molecular dynamics

Revealing Trap States in Lead Sulphide Colloidal Quantum Dots by Photoinduced Absorption Spectroscopy - Kahmann, Simon; Sytnyk, Mykhailo; Schrenker, Nadine; Matt, Gebhard; Spiecker, Erdmann; Heiß, Wolfgang; Brabec, Christoph; Loi, Maria A. (Advanced Electronic Materials, 2017)
Due to their large surface to volume ratio, colloidal quantum dots (CQDs) are often considered to exhibit a significant amount of surface defects. Such defects are one possible source for the formation of in-gap states (IGS), which can enhance the recombination of excited carriers, i.e., work as electrical traps. These traps are investigated for lead sulphide CQDs of different size, covered with different ligands using a mid-infrared photoinduced absorption (PIA) technique. The obtained PIA spectra reveal two distinct absorption bands, whose position depends on the particle size, i.e., the electronic confinement in the CQDs. Smaller particles exhibit deeper traps. The chemical nature of the capping ligand does not affect the resulting position other than due to its change in confinement, but better passivating species lead to smaller signals. Furthermore, ligand specific narrow lines observed are superimposed on the broad electronic background of the PIA spectra, which is attributed to Fano resonances caused by the interplay of the narrow molecular vibrations and the continuum of trap states. Mid-infrared photoinduced absorption represents a valuable tool to unravel distributions of IGS in CQDs and allows for an assessment of the quality of ligand exchanged films. These findings have implications for understanding the performances of CQD-based (opto-) electronic devices, such as solar cells, transistors, or quantum dot light emitting diodes, which are limited by frequent carrier trapping events.
Keywords: Colloidal quantum dots; Mid infrared spectroscopy; Molecular vibrations; Pump-probe spectroscopy; Trap states